Tuning oxygen vacancies in MoS2@MoO2 hierarchical tubular heterostructures for high performance lithium-ion batteries. (10th October 2022) - Guo, Chaofei; Yao, Yaomeng; Cao, YingNan; Feng, Qin; Zhang, Yifan; Wang, Yong
Abstract : Molybdenum disulfide (MoS2 ), with its unique two-dimensional nanostructure and high theoretical capacity, is considered a promising electrode for lithium-ion batteries (LIBs). Abstract : Molybdenum disulfide (MoS2 ), with its unique two-dimensional nanostructure and high theoretical capacity, is considered a promising electrode for lithium-ion batteries (LIBs). However, the disadvantages of MoS2 electrodes include low electronic conductivity, sluggish cation kinetics, serious volume change, poor cycle stability, and inefficient rate performance of lithium storage. Herein, oxygen vacancy and heterostructure engineering are rationally involved in revealing the moderate oxygen vacancy in the hierarchical tubular heterostructure material (MoS2 @MoO2 ) via a self-template method as a highly active LIB electrode. Due to the presence of the moderate oxygen vacancies and heterojunction structure of MoS2 @MoO2 -4, the diffusion pathway and barrier for lithium ions can be significantly reduced, accelerating the ionic diffusion rate and further promoting the reaction kinetics. The electrode achieves a high reversible capacity of 1200.1 mA h g −1 at 100 mA g −1 after 100 cycles with the optimum regulation of the sulfur contents and the moderate oxygen vacancy (MoS2 @MoO2 -4). Additionally, good rate capability is obtained at stepwise current densities due to the merits of MoS2 @MoO2 . A series of measurements such as EPR, XPS, in situ XRD, and in situ Raman are also employed to reveal the synergistic effect in the midst of oxygen vacancies and heterostructures for lithium storage. All results prove that the moderate oxygen vacancy and tubular heterostructure can implement faster Li + transport and lower the diffusion barrier of lithium ions, resulting in enhanced lithium storage performance of MoS2 @MoO2 .